2015
DOI: 10.1007/s00276-015-1428-5
|View full text |Cite
|
Sign up to set email alerts
|

The anatomic variations of the posterior talofibular ligament associated with os trigonum and pathologies of related structures

Abstract: In patients with os trigonum, the posterior fibers of the PTFL were inserted herein. In the case of an os trigonum signal alterations of ligaments were more common, which may reflect chronic instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…This theory is supported by Gursoy et al's findings in their 2015 retrospective MRI study. In this study, they found an association between the presence of an os trigonum and an increase in signal intensity throughout the lateral ankle ligaments, which pointed towards chronic instability [25]. Despite this, pure ankle dislocation has not been reported as a complication following excision of symptomatic os trigonum without repair of the PTFL insertion.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This theory is supported by Gursoy et al's findings in their 2015 retrospective MRI study. In this study, they found an association between the presence of an os trigonum and an increase in signal intensity throughout the lateral ankle ligaments, which pointed towards chronic instability [25]. Despite this, pure ankle dislocation has not been reported as a complication following excision of symptomatic os trigonum without repair of the PTFL insertion.…”
Section: Discussionmentioning
confidence: 63%
“…Normally, the PTFL short fibers run from the fibula to the lateral talus whereas the long fibers run from the fibula to the posterior-lateral process of the talus [24]. If an os trigonum is present, then the long fibers attach directly onto the os, which is only attached to the talus by a synchondrosis 3 Case Reports in Orthopedics [25]. We hypothesize that this results in an anatomic "weak link" in the ankle due to the synchondrosis being less robust than the bony malleolus and the normal PTFL attachment.…”
Section: Discussionmentioning
confidence: 99%
“…may become symptomatic after a simple sprain, as has been reported for other skeletal variations at the talus, like the os trigonum and talus bipartitus (bipartite talus, frontal cleft). 1,8,20 All of the symptomatic patients in our series and 4 of the 6 symptomatic patients in the literature were adolescents or young adults. Talus secundarius is therefore likely to become symptomatic upon complete ossification.…”
Section: Discussionmentioning
confidence: 74%
“…However, a hitherto asymptomatic ossicle may become symptomatic after a simple sprain, as has been reported for other skeletal variations at the talus, like the os trigonum and talus bipartitus (bipartite talus, frontal cleft). 1,8,20…”
Section: Discussionmentioning
confidence: 99%
“…With respect to these unique functions, the native shape of the talus is also unique and asymmetrical because of its three articulations with the tibia, fibula, navicular bone, and calcaneus. Several ligaments attach the talus to its surrounding articular structures [12]. Based on these exclusive characteristics, the talus is prone to several pathologies and injuries, but the native talus is difficult to reconstruct or duplicate in patients with conditions such as peritalar instability [13], talar bone damage [14], and loss of the talus [2].…”
Section: Plos Onementioning
confidence: 99%